Design is how it works : how the smartest companies turn products into icons. - Greene, Jay, ....- (New York : Portfolio Penguin, 2010)
Introduction 1 Porsche 2 Nike 3 Lego 4 Oxo 5 Rei 6 Clif Bar 7 Ace Hotels 8 Virgin Atlantic 9 The Intersection of Business and Design Conclusion Acknowledgments Further Reading Index